Constraints on asymmetric dark matter from asteroseismology. Issue 1 (January 2016) - Casanellas, J; Lopes, I
Abstract: We report recent results on the impact of asymmetric dark matter (DM) particles on low-mass stars. First, we found that the small convective core expected in stars with masses between 1.1 and 1.3 M⊙ is suppressed due to DM cooling. Moreover, stars with masses below 1 M⊙ have their central temperatures and densities more strongly influenced by DM than in the solar case. We were able to put limits to the DM mass and spin-dependent DM-proton scattering cross section by comparing the modelling of the nearby star α Cen B with photometric, spectroscopic and asteroseismic observations.